PERAN GURU DALAM PEMBENTUKAN KARAKTER SISWA - Marlina Wally (Pascasarjana IAIN Ambon, 2021)
Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System which explains that education is to develop people who have faith and piety, have noble character and have life skills. The main problem raised in this study is what is the role of the teacher in shaping the character of students? This study aims to analyze in depth the teacher's role in the formation of student character. This research is a descriptive qualitative research, namely library research, namely research whose data sources are obtained from various literatures. Data collection techniques were carried out through direct and indirect citation techniques. Data analysis was carried out using content analysis techniques, namely an effort to describe and analyze in depth the content of written or printed information in an objective and systematic manner. The results of the research are that the teacher has three important roles in shaping the character of students, namely, 1) the role of the teacher as an educator must be able to link the subject matter taught with the values of character education; 2) the role of the teacher as a teacher, namely the teacher must choose a learning model that is in accordance with the material being taught so that through this learning model the teacher can shape and assess the character of students; and 3) the role of the teacher as a trainer, namely the teacher as a trainer must be able to provide direct examples in interactions with students on how to have good character, which is in accordance with applicable values and norms.